A Comparison between Vitamin D3 and 25-Hydroxyvitamin D3 on Laying Performance, Eggshell Quality and Ultrastructure, and Plasma Calcium Levels in Late Period Laying Hens - Xiaoqing Jing; Yiwei Wang; Fulong Song; Xianfeng Xu; Mingkang Liu; Yu Wei; Huiling Zhu; Yulan Liu; Jintao Wei; Xiao Xu (Animals, 2022)
The objective of this study was to compare high supplementary doses (125 µg/kg) of vitamin D3 (VD3) or 25-hydroxyvitamin D3 (25-OHD3) with commercial supplementary doses (62.5 µg/kg) of VD3 on laying performance, eggshell quality and ultrastructure, and plasma calcium levels in late period laying hens. A total of 1512 Roman Gray (60-week-old) laying hens were allotted into three treatments with 12 replicates and 42 birds in each replicate. During the 12-week trial period, the layers were fed a basal diet supplemented with different doses of VD3 or 25-OHD3 (62.5 µg/kg VD3 in control group, CON; 125 µg/kg VD3 in high level VD3 group, VD3; 125 µg/kg 25-OHD3 in high level 25-OHD3 group, 25-OHD3). The results showed that high supplementary doses of VD3 or 25-OHD3 increased laying rate (p < 0.05). Moreover, the layers fed high doses of VD3 or 25-OHD3 diets had decreased unqualified egg rate and mortality (p < 0.05). High supplementary doses of VD3 or 25-OHD3 increased eggshell strength and eggshell thickness (p < 0.05). From observation in eggshell ultrastructure, high doses of VD3 or 25-OHD3 diets increased the palisade layer thickness and mammillary knob density (p < 0.05). Furthermore, high doses of VD3 or 25-OHD3 diets increased the calcium levels in plasma (p < 0.05). In summary, compared with 62.5 µg/kg doses of VD3, supplementary 125 µg/kg doses of VD3 or 25-OHD3 improved the laying performance, eggshell quality, and plasma calcium levels in late period laying hens. Additionally, there was an equal effect on laying performance and eggshell quality in the hens fed dietary 125 µg/kg doses of VD3 or 25-OHD3.